About the picture book and its use for pre-school children - Anna Boguszewska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The development of civilization and technology promotes access to visual culture. The complete formation of human personality includes introduction to understanding of cultural communications, requires preparation from the earliest years of life. In the visual education of children the key assumption is the usage of picture books and books with illustrations of artistic character. They constitute the first artistic medium, the primary carrier of aesthetic values. Due to the ubiquity of visual culture in the 21st century, it has a vital significance in the contemporary aesthetic education of a child. Activities of a teacher are often the only chance for a child to learn to draw from cultural heritage of fine arts.